Association of acanthosis nigricans with race and metabolic disturbances in obese women - Araújo,L.M.B. (2002)
Acanthosis nigricans (AN) has been recognized as a marker of insulin resistance and diabetes mellitus. We have compared frequency of race and metabolic disturbances in obese women with several degrees of AN (AN group, N = 190) to a group without AN (non-AN group, N = 61) from a mixed racial population. The groups were similar regarding age and body mass index. All patients (except the diabetic patients) underwent an oral glucose tolerance test (75 g). The racial distribution of this population was 35.1% white, 37.8% mulatto and 27.1% black and the frequency of AN was 62.5, 82.1 and 83.8%, respectively, higher in black versus white (P = 0.003) and mulatto versus white (P = 0.002) women. The frequencies of diabetes mellitus and impaired glucose tolerance were 5.8 and 12.6% in the AN group and 1.6 and 8.2% in the non-AN group, respectively (P>0.05). Fasting glucose, ß cell function determined by the homeostasis model of assessment (HOMA), fasting insulin and insulin area under the curve were similar for the AN and non-AN groups. A higher HOMA insulin resistance was observed in the AN group compared to the non-AN group (P = 0.02) and in the subgroup of highest degree of AN compared to those with other degrees. The mean lipid levels and the frequency of dyslipidemia were similar for the two groups. AN was strongly associated with the black or mulatto rather than the white race, even after taking into account the effect of age, body mass index and HOMA insulin resistance.